Introduction to the special issue - James Rolleston (Studies in 20th & 21st Century Literature, 1997)
Two seemingly superficial questions prompted the initiation of the present extensive survey of contemporary German poetry: what difference has 1989 made to lyrical voices both East and West…
Keywords: superficial; questions; poetry; contemporary German poetry; German; Germany; East; West; German poetry; 1989; lyrical voices